Innovative approaches for deep decarbonization of data centers and building space heating networks : Modeling and comparison of novel waste heat recovery systems for liquid cooling systems - Lu, Tao; Lü, Xiaoshu; Välisuo, Petri; Zhang, Qunli; Clements-Croome, Derek (Elsevier, 2023)
The data usage surge drives greater data center demand, amplifying global CO2 emissions. Mitigating climate change necessitates reducing data center CO2 emissions. Reusing waste heat from data centers offers a potential energy efficiency boost and environmental impact reduction. This study utilizes liquid cooling technology to raise waste heat temperature for building space heating and introduces the concept of ‘data furnaces,’ where data centers directly supply waste heat to heat buildings on-site, reducing district heating consumption and lowering CO2 emissions. Efficiently designing a heat recovery heat exchanger system that accounts for both heat rejection and cooling sides of a liquid cooling system is crucial for achieving complete heat recovery without using heat pump, a commonly overlooked aspect in existing literature. To address this issue, we propose two heat exchanger schemes: connecting the building space heating network to the secondary side (Scheme 1) and the primary side (Scheme 2) of the cooling distribution unit. Implementing these innovations leads to the elimination of dependence on a heat pump, substantially cutting energy and CO2 emissions. Using TRNSYS software, we develop, model, and compare waste heat recovery schemes to curb district heating consumption and CO2 emissions. To demonstrate broad implications of the proposed approaches for energy efficiency and sustainability in the data centers and building space heating networks, a showcase study examines constant 25 kW waste heat from a direct-to-chip liquid-cooled rack in an office building with 285.7 MWh annual space heating demand. A novel waste heat recovery rate relationship graph is created to assist system design, uncovering an unexpected result in Scheme 2: waste heat recovery decreases as outdoor temperature falls. In contrast, Scheme 1 maintains a stable waste heat recovery rate around 25 kW, regardless of outdoor temperature fluctuations. As a result, Scheme 1 reuses 155.2 MWh of waste heat annually compared to 138 MWh for Scheme 2. Schemes 1 and 2 yield annual electricity savings of 2290.5 kWh and 905.2 kWh, respectively, for the cooling system. Both schemes achieve profitability within a year through a 25-year life cycle analysis (LCC) and substantially reduce CO2 emissions, with Scheme 1 saving 291,996 kgCO2 and Scheme 2 saving 258,192 kgCO2. The study addresses critical gaps in existing literature by emphasizes LCC. The proposed heat exchanger designs represent pioneering solutions for optimizing waste heat recovery, particularly in challenging climates. New findings offer substantial benefits to both liquid-cooled and air-cooled facilities, making significant contributions to achieve carbon neutrality in data center operations.
Keywords: Data center waste heat utilization; Liquid-cooled rack; District heating networks; Building space heating; Life cycle cost; Life cycle CO2 emission reduction; fi=Automaatiotekniikka|en=Automation Technology|; fi=Energiatekniikka|en=Energy Technology|